ظاهرة التنمـــر ( اسبابها , انماطها , نظرياتها , اساليب معالجتها ) - خزعل م . د . ميادة عبد الله; علي م . د . إخلاص جواد (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The current research aims to shed light on the problem of school bullying and its spread and to show its weaknesses and damages to deal with it. The research allows to identify the most important forms and forms of school bullying and help students to get rid of it and help the family to identify it and avoid it in the best possible way.